Soil-plant-animal relationships and their effect on pasture-based milk production in Hacienda Cuba, Colombia - María A. López G.; Ana G. Quintero M.; Juan J. Zúñiga E.; Felipe Vélez S.; Juan F. Naranjo R.; Óscar A. Sáenz R.; Andrés F. Pérez R. (Revista Científica)
Milk production from buffaloes has experienced significant growth in Colombia over the past 20 years. These systems are primarily located in the low tropics, where production systems face limitations in intensification. At Hacienda Cuba, situated in Montelíbano, Córdoba, Colombia, various sustainable intensification strategies have been implemented to enhance buffalo milk production. This study describes the soil, plant, and animal components to assess the capacity for high-quality buffalo milk production. We collected soil and forage samples from the grazing area for chemical characterization and quantified the available forage supply. Subsequently, the milk production potential of the animals was determined based on the forage diet provided, as well as the impact and quantification of intensification practices, such as strategic supplementation, on buffalo milk production. Our findings revealed that soil composition was 10% sand, 46% silt, and 44% clay, pH of 5.0, CEC of 15.16, and P of 11. Microbiological analyses indicated that most functional groups were within acceptable ranges. Characterizing the forage component revealed that buffaloes primarily consume a mixture of forages, including Paspalum fasciculatum, Dichanthium annulatum, Brachiaria decumbens, Dichanthium aristatum, Brachiaria arecta, and Panicum virgatum. On average, these forages exhibited the following nutritional quality characteristics: crude protein of 10.25%, neutral detergent fiber of 65.60%, the in vitro digestibility of dry matter was 56.45%, and the metabolizable energy was 2.75 Mcal Kg DM-1. Our results indicate that buffaloes received a substantial forage supply or allocation, ranging between 7 and 8 kg DM/100 kg of live weight. The production potential is based on a pasture yielding 4.04 liters of daily milk with 6% fat. When the intensification practices were adopted (2 kg of balanced feed and 6 kg of sorghum silage), an increase of 78.5% in milk production was observed. These sustainable intensification practices, such as strategic supplementation in dairy buffaloes in Colombia, enhance milk production and may improve milk quality (it needs to be evaluated). Consequently, these prac-tices can potentially increase profit since payment for milk islinked to these parameters.